Expression of the yeast NADH dehydrogenase Ndi1 in Drosophila confers increased lifespan independently of dietary restriction. - Sanz, A.; Soikkeli, M.; Portero-Otín, M.; Wilson, A.; Kemppainen, E.; McIlroy, G.; Ellilä, S.; Kemppainen, K.K.; Tuomela, T.; Lakanmaa, M.; Kiviranta, E.; Stefanatos, R.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Mutations in mitochondrial oxidative phosphorylation complex I are associated with multiple pathologies, and complex I has been proposed as a crucial regulator of animal longevity. In yeast, the single-subunit NADH dehydrogenase Ndi1 serves as a non-proton-translocating alternative enzyme that replaces complex I, bringing about the reoxidation of intramitochondrial NADH. We have created transgenic strains of Drosophila that express yeast NDI1 ubiquitously. Mitochondrial extracts from NDI1-expressing flies displayed a rotenone-insensitive NADH dehydrogenase activity, and functionality of the enzyme in vivo was confirmed by the rescue of lethality resulting from RNAi knockdown of complex I. NDI1 expression increased median, mean, and maximum lifespan independently of dietary restriction, and with no change in sirtuin activity. NDI1 expression mitigated the aging associated decline in respiratory capacity and the accompanying increase in mitochondrial reactive oxygen species production, and resulted in decreased accumulation of markers of oxidative damage in aged flies. Our results support a central role of mitochondrial oxidative phosphorylation complex I in influencing longevity via oxidative stress, independently of pathways connected to nutrition and growth signaling.